Simulation of Friction Stir Extrusion using Smoothed Particle Hydrodynamics (SPH) - Mostafa Akbari; Mansour Hakimollahi; parviz Asadi; Hossein Rahimi Asiabaraki (International Journal of Advanced Design and Manufacturing Technology, 2022)
This research aims to construct a three-dimensional numerical model for modeling friction stir extrusion using the completely Lagrangian method, smoothed particle hydrodynamics (SPH). For extrusion simulations, the Finite Element Method (FEM) is extensively utilized; however, it has limitations due to excessive element deformation. Because the particle-based method eliminates the usage of volumetric elements, SPH can be a viable alternative. The performance of the SPH model was evaluated using different particle sizes. The results showed that the smaller particle size improves the temperature results as well as the shape of the wire produced. Then the mechanical and microstructural properties of the produced wires were investigated. The results show that the grain size in the center of the wire is larger than its perimeter due to the lower strain rate in this area. Increased strain reduces grain size in the produced microstructure by increasing nucleation sites during recrystallization, as is well known. The wire microhardness in the centre is 121 HV, whereas it is 129 HV in the periphery. Grain size is the main reason of increased hardness near the sample's periphery.